Multilocular thymic cyst in a patient with preclinical rheumatoid arthritis: A case report. (2020) - Kawamoto, Nobutaka; Okita, Riki; Inokawa, Hidetoshi; Murakami, Tomoyuki; Okabe, Kazunori
Highlights: Inflammatory conditions cause multilocular thymic cyst. Causes of the inflammation include autoimmune diseases or malignant tumors. Evaluating the cause of inflammation in multilocular thymic cyst is essential. First reported multilocular thymic cyst with preclinical rheumatoid arthritis. Early treatment of rheumatoid arthritis prevents irreversible disability. Abstract: Introduction: Multilocular thymic cyst (MTC) is a rare condition of an acquired multilocular cystic lesion caused by inflammation and often associated with autoimmune diseases or malignant tumors. We present a patient with MTC and asymptomatic rheumatoid arthritis (RA), which is termed preclinical RA. Presentation of case: A 60-year-old man underwent a computed tomography scan, which revealed an 8.5 cm multilocular cystic lesion in the anterior mediastinum. The tumor had a lower intensity on T1-weighted imaging and a higher intensity on T2-weighted imaging. The imaging did not only suggest an MTC, but also the possibility of a thymoma with cystic degeneration, or lymphoma. We performed an extended thymectomy via median sternotomy. The lesion was diagnosed as MTC based on histopathological findings. Laboratory tests were performed for the purpose of screening for autoimmune diseases. He was diagnosed with preclinical RA, since the anti-cyclic citrullinated peptide antibody (ACPA) was positive. Discussion: Specificity of ACPA is recorded in over 90% of patients with RA; ACPA is positive in about 40% of patients with preclinical RA. As patients with preclinical RA are more likely to develop RA, careful follow-up is required. Early diagnosis and treatment of RA can prevent destruction of joints, thereby preventing irreversible disability. Conclusion: In patients with MTC, evaluating the cause of the inflammation, such as autoimmune diseases, is essential. Further studies are required to investigate the relationship between MTC and preclinical RA.